Politics on display: The realities of artisanal mining formalisation in Ghana. Issue 4 (December 2021) - Ofori, Alesia D.; Mdee, Anna; Van Alstine, James
Highlights: The display of politics and power dynamics by politicians, state actors and military officials are at the centre of the failure of formalisation reforms in Ghana. Government officials, politicians and miners operating at both local and national levels exploit these agendas for a range of political and economic objectives. Artisanal mining regulation and formalisation thus generates messy political outcomes beyond its technical agenda. Abstract: This paper demonstrates how politics mediate the formulation and everyday implementation of formalisation within the informal artisanal mining space in Ghana. It employs ethnographic methodologies to examine micro-events that occurred in a Ghanaian mining community during the implementation of deterrent formalisation intervention from 2017 to 2020. By focusing on the display of everyday practical norms and politics, the paper argues that despite the repetitive enactment of the ASM formalisation discourse by the state, informality within ASM persists because of the visible display of practical norms enacted by myriad political actors with competing political and material interests. The paper contributes to the ongoing debate on the gap between the theory and practice of formalisation, especially in Sub-Saharan Africa. The paper makes a call for both policy and academic discourse on ASM to critically engage with the complex state-society interaction and how the display and distribution of power amongst actors thwart formalisation objectives.